Lithium splashing from flowing liquid lithium limiter and its effect on high confinement plasma performance in EAST tokamak. (December 2020) - Tang, Z.L.; Zuo, G.Z.; Li, C.L.; Maingi, R.; Meng, X.C.; Xu, W.; Sun, Z.; Qian, Y.Z.; Huang, M.; Zhang, D.H.; Andruczyk, D.; Tritz, K.; et al.
Highlights: Liquid Li splashing from FLiLi limiter on EAST was observed in L/H-mode discharges. Li splashing was due to Rayleigh-Taylor instability, resulting from J → × B → forces. Li splashing in low-parameter plasma caused obvious degradation of plasma performance. High-parameter plasma has higher tolerance to Li impurity. Decrease in limiter plate angle and Li contamination facilitate the Li splashing. Abstract: To study the potential applications of liquid lithium (Li) as plasma facing material, the third generation of flowing liquid Li (FLiLi) limiter has been designed and successfully tested in EAST tokamak H-mode discharges in the 2018 run campaign. The stability of liquid Li on FLiLi surface, and Li splashing and its effect on the plasma performance are investigated in detail. Li splashing was observed in L-mode and H-mode discharges due to Rayleigh-Taylor (R-T) instability, resulting from electromagnetic forces J → × B → . Li splashing in low-parameter plasma decreased both core and edge electron temperatures, resulting in the degradation of plasma energy confinement and even H-L back transition, however, it almost did not influence plasma confinement performance in high-parameter plasma. These findings indicate that high-parameter plasma has higher tolerance to Li impurities than low-parameter plasma. By contrast, tungsten splashing from the melted layer on the upper divertor was also induced by the R-T instability but generally resulted in plasma disruption, which suggests lower tolerance to tungsten impurities in EAST tokamak.